Herkules Poirot i marny kryminał. Na marginesie powieści Agathy Christie „Morderstwo w Orient Expressie” (1934) - Anna Gemra (Literatura i Kultura Popularna, 2025)
In the late 1920s, detective fiction was entering its golden age and already had a huge readership. In addition to original crime stories, many highly formulaic works began to appear, whose authors had no ideas of their own, but wanted to use the publishing and financial success of the crime story for their own purposes. Eventually, several sets of rules were created (most famously by S.S. Van Dine and Ronald Knox) intended for writers meaning to craft a good crime story. In Murder on the Orient Express, Agatha Christie reached for many solutions well known to readers from ‘poor crime stories,’ such as the appearance of the murderer, basing the investigation on hunches instead of deduction, introducing more than one villain, etc. She invited readers to a game, the stakes of which were solving a seemingly completely formulaic, but in fact extremely sophisticated murder mystery.